Psychological analysis of social structure - Wright, George Gibson Neill (The University of Edinburgh, 1933)
It is an unfortunate result of the semi - practical aims which naturally influence social philosophers, that they are apt throughout to take up an indifferent, if not a hostile, attitude to their given object. They hardly believe in actual society as a botanist believes in plants, or a biologist in vital processes. And hence, social theory comes off badly. No student can really appreciate an object for which he is always apologising... It is in no spirit of obscurantism ... that some t.ke up a different position. They are convinced that an actual living society is an infinitely higher creature than a steam -engine, a plant, or an animal; and that the best of their ideas are not too good to be employed in analysing it.